ANALISIS ELEKTROFASIES BERDASARKAN DATA WELL LOGGING DALAM MENENTUKAN LINGKUNGAN PENGENDAPAN BATUBARA DI AREA PT BHUMI SRIWIJAYA PERDANA COAL, MUSI BANYUASIN, SUMATRA SELATAN - Setiawan, Rendy Agus; Adhitya, Bagus; Amin, Sarwo Sucitra (Prodi Fisika FST UNJA, 2025)
Musi Banyuasin Regency is one of the areas in South Sumatra which has very abundant natural Coal resources. Coal still plays a very important role as a natural resource that is much needed, so it is important to know the aspects of Coal starting from the quality and characteristics of Coal as well as the Coal formation process. So it is necessary to determine the Coal deposition environment. This aims to provide additional information and to determine the characteristics of Coal so that it can provide additional information. In this study, secondary data was used in the form of LAS data files resulting from recording well logging data for 7 wells which were then processed using WellCAD 5.5 software to obtain log sheet results, namely gamma ray logs and density logs, which were then interpreted as subsurface lithology by reading the deflection log curve. From the results of reading the log curve, the lithology in the research area was obtained in the form of mudstone, siltstone, sandstone and Coal. Analyzing the grain size variations of the lithology in the research area using the electrofacies analysis method, it was found that three dominant depositional patterns in the research area were of the Serrated, Cylindrical and Symmetrical types when compared with Horne calcification. As well as Levee in hard rock, clay. And from the facies analysis it can be identified that the research area is a Delta depositional environment in the Upper Delta Plain-Fluvial zone.